Trisomy 13, home health-care and multidisciplinary approach: Case report - Patrícia Zschaber Anacleto; Virginia Araújo de Sousa; Julliane V Joviano-Santos (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To recognize and address Patau's syndrome, despite its rarity and associated low life expectancy, through the presentation of a case study of a 2-year-old patient receiving Home Care services. Case description: We present a female patient who defied the odds with a prolonged survival, possible due to Home Care. She was delivered via cesarean section at 31 weeks + 4 days due to restricted uterine growth. The mother, aged 36, had received proper prenatal care and was in good health. The diagnosis of Patau's syndrome was confirmed through karyotyping after birth. Despite the severe clinical nature of the case, the patient, now with two years old, receives specialized home-based care, supported by a tracheostomy and gastrostomy. A dedicated 24-hour nursing technician ensures continuous monitoring, and the patient benefits from regular medical check-ups, physiotherapy five times a week, weekly speech therapy sessions, monthly consultations with a nutritionist, and ongoing psychological support for her family members. Comments: This multidisciplinary approach has resulted in a slight motor response, highlighting the positive impact of comprehensive care on her overall well-being. The existence of a robust support network for families facing similar challenges is crucial, and a multidisciplinary care can effectively prevent complications associated with this impactful syndrome.